YY1-Targeted RBM15B Promotes Hepatocellular Carcinoma Cell Proliferation and Sorafenib Resistance by Promoting TRAM2 Expression in an m6A-Dependent Manner - Tan, Chunzhong; Xia, Peng; Zhang, Hao; Xu, Kequan; Liu, Pengpeng; Guo, Deliang; Liu, Zhisu (Frontiers in Oncology, 2022)
As one of the most common internal modifications in eukaryotic mRNA, N6-methyladenosine (m6A) modification is involved in the pathogenesis of many diseases, including hepatocellular carcinoma (HCC). In this study, we explored the prognostic significance of the expression of RNA binding motif protein 15B (RBM15B) in HCC, by studying specimens collected from clinical subjects. RBM15B is highly expressed in HCC patients and indicates a poor prognosis. Functionally, overexpression of RBM15B promotes HCC cell proliferation and invasion and induces sorafenib resistance in HCC cells. Mechanistically, we confirmed that RBM15B is transcriptionally activated by YY1 and regulates the stability of TRAM2 mRNA in an m6A-dependent manner. Overall, our results reveal a YY1-RBM15B-TRAM2 regulatory axis and highlight the critical role of RBM15B and m6A modifications in HCC. These findings may provide a novel mechanism and therapeutic targets for the treatment of HCC.